Kecenderungan BDD pada laki-laki anggota gym: Adakah peran perfeksionisme dan konsep diri? - Mareta, Zafira Dwi; Santi, Dyan Evita; -, Rahma Kusumandari (JIWA: Jurnal Psikologi Indonesia, 2024)
Abstract This study aims to determine the relationship between perfectionism and self-concept with the tendency of Body Dysmorphia Disorder in male users of Gym services. This research is a type of quantitative research using correlational quantitative methods. The technique of taking participants in this study used Incidental sampling. Participants in this study were 124 respondents with criteria aged 18-30 years. Perfectionism measurement uses a modified BTPS (Big Three Personality Scale) scale into Indonesian based on the perfectionism scale according to Saklofske, et al. Measurement of self-concept data uses a scale based on the theory put forward by Carl Rogers. In addition, the measurement of Bpdy Dysmorphic Disorder tendency data is based on aspects of the theory put forward by Phillips. The results of statistical analysis of the relationship between perfectionism and self-concept variables simultaneously on the tendency of Body Dysmorphia Disorder shows that there is a significant relationship between the independent variables to the dependent between perfectionism and self-concept with the tendency of Body Dysmorphia Disorder. Partial test results on perfectionism variables shows that there is a significant positive relationship between perfectionism and the tendency of Body Dysmorphia Disorder so that the higher the perfectionism, the higher the tendency of Body Dysmorphia Disorder owned. While the partial test results on the self-concept variable shows that there is a significant negative relationship between self-concept and the tendency of Body Dysmorphia Disorder. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara perfeksionisme dan konsep diri dengan kecenderungan Body Dysmorphia Disorder pada laki-laki pengguna layanan Gym. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan metode kuantitatif korelasional. Teknik pengambilan partisipan dalam penelitian ini menggunakan Incidental sampling. Partisipan dalam penelitian ini sebanyak 124 responden dengan kriteria berusia 18 – 30 tahun. Pengukuran perfeksionisme menggunakan modifikasi skala BTPS (Big Three Personality Scale) menjadi bahasa indonesia berdasarkan skala perfeksionisme menurut Saklofske,dkk. Pengukuran data konsep diri menggunakan skala yang berdasarkan teori yang di kemukakan oleh Carl Rogers. Selain itu, pengukuran data kecenderungan Bpdy Dysmorphic Disorder didasarkan pada aspek teori yang dikemukakan oleh Phillips. Hasil analisis statistika hubungan variabel perfeksionisme dan konsep diri secara simultan terhadap kecenderungan Body Dysmorphia Disorder, terdapat hubungan antara variabel bebas ke terikat yang signifikan antara perfeksionisme dan konsep diri dengan kecenderungan Body Dysmorphia Disorder. Hasil uji parsial pada variabel perfeksionisme menunjukkan terdapat hubungan positif yang signifikan antara perfeksionisme dengan kecenderungan Body Dysmorphia Disorder sehingga semakin tinggi sifat perfeksionisme, maka semakin tinggi kecenderungan Body Dysmorphia Disorder yang dimiliki. Sedangkan hasil uji parsial pada variable konsep diri menunjukkan terdapat hubungan negatif yang signifikan Antara konsep diri dengan kecenderungan Body Dysmorphia Disorder.